Regulation Of The Minister Of National Education Republic Of Indonesia Number 24 Of 2007 Concerning Standards And Infrastructure Standards For Sd / Mi, Smp / Mts, And Sma / Ma - Akhmad Akromusyuhada (BULLET : Jurnal Multidisiplin Ilmu, 2022)
This article explains the regulation of The Ministry of National Education of The Republic of Indonesia Number 24, year 2007 about The Fascilities and Infrastructures Standards for all levels of education in Indonesia (public and religious school) : elementary school, junior high school, and senior high school that has a big impact on the application of Islamic education institution. Especially on the Islamic schools of which don’t apply the concept of Islamic architecture that is “The Way of Life”. This article uses literature research. The result of this research shows that Islamic architectural concept can be applied because it does not violate the rules of architecture planning and desingning which consist of five components: 1. Function, 2. Form, 3. Technics, 4. Safety, 5. Comfort. The conclusion is it is important for the Islamic education institution to apply the Islamic architectural concept in fulfilling the needs of fascilities and infrastructure as long asit’s not against the main rules that has been endorsed in the regulation of The Ministry of National Education of The Republic of Indonesia Number 24, year 2007 about The Fascilities and Infrastructures Standards for all levels of education in Indonesia (public and religious school) : elementary school, junior high school, and senior high school in order that Islamic education institution has its own features that show the true Islamic characteristics.